THE STUDY OF METAPHORS IN UZBEK LINGUISTICS BASED ON PROSE TEXTS - Ruziyeva Nigora Sapar qizi (Web of Journals Publishing, 2023)
The article introduces primary school students to the expressive features and facets of the meaning of metaphors used in narrative texts. There was also a scientific study of aspects demonstrating the unique expressive capabilities and skill of the writer. The pragmatic possibilities of productive use of metaphor in literary texts, especially in works of the great epic genre, have been studied lyrically.
Keywords: prose text, teaching methods, literary text, discourse, metaphorical meaning, novel, epic works, facets of meaning, methodological possibilities, pragmatic analysis, linguistic research, connative meaning, dialogue